Relationship between organisational culture and knowledge management: Scenario of a Malaysian Public Institution of Higher Learning. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2007)
The Ninth Malaysia Plan or RMK9, as it is more popularly known, signifies yet another key attempt of the Government to hasten the development of the nation into a knowledge-based economy (k-economy)in order to achieve the objectives of Vision 2020.